A proposed entrance examination in elementary science for elementary school graduates seeking admission at the Central Luzon Teachers College High School Department - Camacho, Basilisa B. De Vera 1939- (1977)
The purpose of the study was to propose and construct an entrance test in elementary science for elementary school graduates who would like to enroll at the Central Luzon Teachers College High School Department. The methods done in the study were pre-planning, planning, writing, and try-out phase. The study concluded that the test constructed has face validity because the test items are all relevant to elementary science as a subject in the elementary curriculum. The test possesse content validity because the areas were represented. It can be safely concluded that the tems included are related to the objectives in the curriculum guide for science in the grade VI level.